(untitled) (PUBMET, 2022)
Scholars have long recognized the potential of a university repository as a new avenue of open access publishing and creating university-led journals (Bankier & Perciali, 2008). The relationship between repositories and journals is not new; an overlay journal, which acts as an “overlay” of a repository adds value to deposited publications through the peer-review process (Cassella & Calvi, 2010). In 2018, the University of Split (UNIST) recognized the potential of both models and founded the ST-OPEN overlay journal with the aim to train students in research and increase the visibility of their own research by publishing student theses after a rigorous, two-round peer-review process and translation into English (Marušić, Tomić, Gudelj, Wager, & Marušić, 2019). By 2022, two full volumes have been published, containing 23 original research articles and four editorials. Our 2021 editorial analysis discovered that the articles available on our OJS website and the Hrčak database were downloaded or visited 2472 times and that the journal had 10,153 visits overall (Gudelj, Ursić, Tomić, & Marušić, 2021). As members of the editorial team, we actively conduct editorial research to identify good practices and possibilities for improvement of our editorial and publication processes. By 2022, the 23 articles and four editorials published were downloaded or visited 13,810 times and a total of 132 manuscripts (original research articles only) were submitted to ST-OPEN. Of the 132 manuscripts, 102 (77.3%) had been previously deposited in the UNIST repository or the Croatian Dabar repository. Most submitted manuscripts (n=108, 81.8%) were students’ graduate theses. As the ST-OPEN editorial team actively screens Croatian repositories for acceptable theses (Marušić et al., 2019), most manuscripts were found through this method (n=59, 44.7%), yet a substantial number was also recommended by the editorial board (n=48, 36.4%) and submitted directly (n=25, 18.9%). While screening the repositories, we encountered the issue of access to deposited theses: 60 were open access (45.5%) and 40 limited access (30.3%) requiring institutional account to be downloaded. Fortyseven were withdrawn by authors during transformative review (35.6%), and 36 rejected by editors (27.3%). Considering that 25 (18.9%) manuscripts were published (including two published in 2022) and 8 (6.0%) were in copyediting or various other stages of review, a total of 92 (69.6%) manuscripts were rejected or the authors opted out of publishing. As ST-OPEN is a cross-department multidisciplinary journal, the published manuscripts came from various scientific fields. Most theses (n=47, 35.6%) came from humanities and social sciences, closely followed by those from biomedical and natural sciences (n=45, 34.0%). Given the high quality of the published manuscripts, the average acceptance rate, and the high number of visits and downloads in the first two years of publishing, we believe we have considerably increased the visibility of student research at UNIST. Without our journal, most theses would never be published outside the repository. Given the positive effect a journal’s tutorship can have on research skills, publication outcomes, and career advancement (Marusic, Markulin, Lukic, & Marusic, 2006; Šimić et al., 2021), we plan to continue and improve our role as educators and author facilitators (Marusic et al., 2004; Marušić et al., 2019). Some issues observed after the first published volume (Gudelj et al., 2021), such as difficulties in accessing theses and lack of contact information for authors, are still a barrier to our access to student theses. We will actively look for the ways to overcome these barriers and improve publication activities and visibility of UNIST students.